Termite Diversity in Ecuador: A Comparison of Two Primary Forest National Parks. Issue 1 (9th January 2020) - Dahlsjö, Cecilia A L; Valladares Romero, Cynthia S; Espinosa Iñiguez, Carlos-Iván
Abstract: Termites are one of the key ecosystem engineers in tropical forests where they play a major role in decomposition rates, both above and belowground. The interest in termite ecology and biogeography has increased in the last few decades; however, the lack of comparable data has limited the wider impact of termite research. For Ecuador, termite studies are relatively rare and comparable data that are collected using standardized sampling methods are missing. In this study, we aim to 1) provide comparable data of termite species and feeding-group diversity from two primary forests in Ecuador and 2) explore the differences in termite species and feeding-group diversity between the two forest sites. Sampling took place in the national parks of Yasuní and Podocarpus where three belt transects (100 × 2 m) following Jones and Eggleton (2000) were conducted in each forest. We found that termite species richness was higher in Yasuní (56 species) than in Podocarpus (24 species) and that 57% of the sampled termite genera had never previously been recorded in Ecuador. The inter-site species dissimilarity was almost complete (Bray Curtis (±SD), 0.91 ± 0.01), which may have been linked to the difference in tree density and species richness in the two forests. Termite feeding-groups diversity was significantly higher in Yasuní than in Podocarpus with the exception of soil-feeding termites which may have been due to competition between humus- and soil-feeding species.